2007
DOI: 10.1590/1808-1657v74p3372007
|View full text |Cite
|
Sign up to set email alerts
|

Virulência De Nematóides Entomopatogênicos (Nemata: Rhabditida) Contra Larvas Da Mosca-Dos-Fungos Bradysia Mabiusi (Lane, 1959) E Persistência De Heterorhabditis Indica Poinar Et Al. 1992 Em Substratos Orgânicos

Abstract: RESUMO Foi avaliada, em condições de laboratório, a virulência de quatro isolados de nematóides entomopatogênicos contra larvas de 3º e 4º instares de Bradysia mabiusi Lane, e a persistência de Heterorhabditis indica Poinar et al. 1992 em substratos orgânicos, dentro de casa de vegetação. No teste de virulência, foram avaliados os isolados H. indica IBCB-n05, Heterorhabditis sp. IBCB-n10, Steinernema glaseri CCA e S. carpocapsae CCA. Os nematóides foram usados na dosagem de 200 juvenis infectivos (JI)/larva. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
1
0
0
1
Order By: Relevance
“…5). These findings agree with Leite et al (2007), when H. indica was used for controlling Bradysia mabiusi larvae at concentration of 5.7 and 22.6 IJ/cm 2 and the efficiency reaching 75 and 85% in green house, and also with Lalramliana and Yadav (2010) by using concentration of 50 IJ/host and the mortality was 100% after 96 h. Lalitha et al 2018 reported that following infection of the host, H. indica releases symbiotic bacteria, which produce and release several toxin complex resulting in activation of immune response such as antimicrobial peptides, phenoloxidase systems, antioxidant and detoxification enzyme, or causing insect mortality.…”
Section: Assessment Of Virulence Against G Mellonella and Penetration...supporting
confidence: 91%
“…5). These findings agree with Leite et al (2007), when H. indica was used for controlling Bradysia mabiusi larvae at concentration of 5.7 and 22.6 IJ/cm 2 and the efficiency reaching 75 and 85% in green house, and also with Lalramliana and Yadav (2010) by using concentration of 50 IJ/host and the mortality was 100% after 96 h. Lalitha et al 2018 reported that following infection of the host, H. indica releases symbiotic bacteria, which produce and release several toxin complex resulting in activation of immune response such as antimicrobial peptides, phenoloxidase systems, antioxidant and detoxification enzyme, or causing insect mortality.…”
Section: Assessment Of Virulence Against G Mellonella and Penetration...supporting
confidence: 91%
“…against S. litura andP. xylostella (Salem et al, 2007); H. indica against larvae of the fungus gnat Bradysiamabiusi (Diptera: Sciaridae) (Leite et al, 2007); H. indica against the rice leaf folder Cnaphalocrosis medinalis (Lepidoptera: Crambidae) (Sankar, 2009); S. carpocapsae against 3 rd and 5 th instar nymphs and adults of S. gregaria (Youssef, 2014) et al, 2020), S. glaseri against the 6 th instar of S. frugiperda (Meka et al, 2020) and S. feltiae HR1 and H. bacteriophora HR2 against P. brassicae (Kasi et al, 2021).…”
Section: I3 Increasing Insect Mortality Rate With Prolonged Time Of E...mentioning
confidence: 99%
“…A virulência de nematoides entomopatogênicos a diferentes insetos foi comprovada com o passar dos anos em diferentes estudos (LEITE et. al., 2005;CAVALCANTI, 2006;LEITE et. al., 2007;MINAS, 2008;CANESIN, 2011;LEITE et.al., 2012;ANDALÓ et.…”
Section: Nematoides Entomopatogênicosunclassified